Deciphering the prognostic significance of WDR77 in gliomas: a comprehensive analysis - Hanwen Lu; Bingchang Zhang; Wenhua Li; Zhanxiang Wang (Scientific Reports)
Abstract Biologically, the WDR77 gene is implicated in the occurrence and development of various clinical malignant tumors. However, its precise role in glioma remains unclear. Therefore, in this study we aimed to perform a comprehensive analysis of the biological functions of WDR77 in glioma. Transcriptome data was obtained from CGGA (mRNAseq-693, mRNAseq-325) and TCGA databases for analysis. A total of 699 glioma samples from the TCGA database were used as the training cohort, while 1018 samples from CGGA were used as the validation cohort. Our analysis revealed that WDR77 was significantly overexpressed in high-grade gliomas and mesenchymal subtype gliomas. Survival analysis indicated that elevated WDR77 gene expression was associated with poor prognostic outcomes for high-grade gliomas, particularly Glioblastoma (GBM). Gene co-expression analysis demonstrated a high correlation between WDR77 and glioma cell cycle, metabolism, and immune processes. Overall, we identified WDR77 as a new biomarker closely associated with the malignant phenotype and poor prognostic outcomes for glioma, playing an important role in regulating the cell cycle and immune processes.